Reconstruction of Macroscopic Maxwell Equations A Single Susceptibility Theory - Cho, Kikuo. (Springer Tracts in Modern Physics, 2010)
This book presents a logically more complete form of macroscopic Maxwell equations than the conventional ones by applying long wavelength approximation to microscopic nonlocal theory. This scheme requires only one susceptibility tensor describing electric and magnetic polarizations together with their mutual interference. The quantum mechanical expression of the susceptibility covers both chiral and achiral symmetry. Only in the absence of chiral symmetry, this reduces to the conventional form, under the additional condition of using magnetic susceptibility defined with respect to, not H, but B. This scheme solves various problems inherent to the conventional scheme of Maxwell equations.